Membangun Kebijakan Kinerja Prima Perencanaan Peningkatan Kinerja (Ppk) Dalam Pendekatan Perbaikan Peningkatan Kinerja Yang Manusiawi - Mauricefle, Alfian; Nugroho, Arif Ganda (Yayasan Pendidikan Tanggui Baimbaian, 2023)
This research is a type of literature that is carried out by collecting data, information, and various other data contained in the literature. This study describes the development of prime performance policies for performance improvement planning (PPK) in the performance improvement approach. The discussion is directed to how efforts are being made to improve performance. Meanwhile, research information is informants who understand efforts to improve performance and other information that can support explanations. Performance improvement brings together individual, team and organizational performance targets. Creating linkages between these targets is the first step of the performance planning model. The performance planning model presents a step-by-step process for producing individual work plans. First, it is done by gathering the information needed to produce an effective plan. Second, the at the team and individual levels, and reflects the new plan. Third, conceptualize the actual individual plan. Fourth, negotiate and finalize the plan.